2020
DOI: 10.1038/s41598-020-62611-w
|View full text |Cite
|
Sign up to set email alerts
|

Water Polishing improved controlled-release characteristics and fertilizer efficiency of castor oil-based polyurethane coated diammonium phosphate

Abstract: The production cost of controlled-release fertilizers is an important factoring limiting their applications. To reduce the coating cost of diammonium phosphate (DAP) and improve its nutrition release characteristics, the fertilizer cores were modified by water polishing with three dosages at 1, 2, and 3%. The effects of modification were evaluated in terms of particle hardness, size distribution, angle of repose and specific surface area. Castor oil-based polyurethane was used as coating material for fertilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The leaching tendency of HB was in agreement with former research on biochar leaching properties [44] and it can be predicted that additional phosphorus would be released with further batching. However, after being crosslinked and interpenetrated by the polyurethane, the release of phosphorus from the internal biochar was prevented, as previously reported [27]. PCB's first round of phosphorus leaching accounted for 44.65-54.85% of the total released quantities and the released quantities were only in the range of 2.67-3.16% for HB.…”
Section: Phosphorus Leachingsupporting
confidence: 68%
See 1 more Smart Citation
“…The leaching tendency of HB was in agreement with former research on biochar leaching properties [44] and it can be predicted that additional phosphorus would be released with further batching. However, after being crosslinked and interpenetrated by the polyurethane, the release of phosphorus from the internal biochar was prevented, as previously reported [27]. PCB's first round of phosphorus leaching accounted for 44.65-54.85% of the total released quantities and the released quantities were only in the range of 2.67-3.16% for HB.…”
Section: Phosphorus Leachingsupporting
confidence: 68%
“…Additionally, polyurethane, as a coating material, will prolong the nutrient release period of inner fertilizers in agriculture and reduce their leaching quantities [ 27 ]. Combined with fertilizers, polyurethane composite material has a high potential to preserve moisture and fertility for the amelioration of desertification [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient release curve of CDAP ( Figure 1A ) is similar to the sigmoidal nutrient uptake curve of maize ( Bender et al, 2013 ). Lu et al (2020) reported similar results pertaining to the nutrient release characteristics of CDAP that match with the nutrient uptake requirement of maize much better than the conventional P fertilizer. Based on soil available P changes during maize growth ( Figure 3A ), it is speculated that CDAP had a longer P-release period in the pot experiment than in the laboratory incubation ( Figure 1A ).…”
Section: Discussionmentioning
confidence: 58%
“…We used an enzyme-linked immunosorbent assay (ELISA) [ 29 , 30 , 31 ] to determine the endogenous hormone (IAA, GA, CTK, ABA, ETH, JA, SA) contents in peel samples, and the specific operations were carried out according to the instructions of individual ELISA kit from Shanghai Heng Yuan Biological Technology Company. Each sample was assayed with three replicates.…”
Section: Methodsmentioning
confidence: 99%